A crosstalk between Na+ channels, Na+/K+ pump and mitochondrial Na+ transporters controls glucose-dependent cytosolic and mitochondrial Na+ signals. Issue 2 (February 2015) - Nita, Iulia I.; Hershfinkel, Michal; Lewis, Eli C.; Sekler, Israel
Graphical abstract